ANALISIS KUALITATIF PELATIHAN LPK PUTRI AYU MANDIRI BERDASARKAN MODEL FOUR LEVEL FRAMEWORK - Urip Sewdyowidodo (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to analyze the training of DUDI (Industrial Business) Internshipparticipants at LPK Putri Ayu Mandiri. The analysis was carried out using the FourLevel Framework model. Data based on apprenticeship and course participants. Theanalysis was carried out by comparing the results between before and after theparticipants attended the training. The results of this study indicate that theobjectives/objectives of this training were achieved which can be seen in the qualityand understanding of the training materials. For tangible benefits, this trainingsucceeded in improving the quality of participants as seen from the results of theirreport accuracy. Meanwhile, for intangible benefits, this training succeeded inincreasing the motivation of participants as seen from their level of adherence. It canbe concluded that the training of participants is able to make a major contribution interms of organizational performance. Thus, participant training deserves to be one ofthe organizational trainings that must be continued to improve the quality of humanresources, especially DUDI apprenticeship participants at LPK Putri Ayu Mandiri